Simple productivity indices for lake ecosystems the case of Sampaloc lake. - Pempengco, Amalia Manrique (Discussion paper / Renewable Resource Economics and Management Research Program, 1989)
Summary of an MSES thesis... presented in the RREM seminar series... February 16, 1989 at the IESAM seminar room, UPLB, College, Laguna.